Cladode size and collection time for pitahaya propagation - Rodrigues, Maria Gabriela Fontanetti [UNESP]; Ferreira, Antonio Flávio Arruda; Malagutti, Emely da Silva [UNESP]; Pinto, Milena Dos Santos [UNESP]; Monteiro, Laís Naiara Honorato [UNESP]; de Sá, Marco Eustáquio [UNESP] (FapUNIFESP (SciELO), 2021)
Cutting is a propagation method with the advantages of early production and uniform cultivation. Some factors influence propagation and rooting, such as the cutting size and the time of year the collection is performed. Thus, the present work aimed to evaluate the ideal size of white-fleshed red pitahaya cladodes and the time of their collection for crop propagation by cutting in view of the physiological quality of the produced clonal plants to enable more appropriate cultural management and increase the cultivation area. The experiment was conducted at the Faculty of Engineering (UNESP) using three cladode sizes (cuttings) with lengths of 10, 20 and 40 cm collected in two seasons (summer and winter). The experimental design used was completely randomized in a split-time scheme, with no dependence on the factors and 20 replicates. Evaluations of the biometric factors related to sprouts and cladode rooting were carried out 60 days after cutting. According to the results, there were significant differences among treatments, with a significant interaction of the number of sprouts. It can be concluded that, regarding the size of the cladodes, it is recommended, when possible, to use cladodes 40 cm in length; regarding the time of collection, it is recommended that collection be conducted in the winter period to favor the development of better-quality clonal plants.
Tamanho e época de coleta de cladódios para propagação de pitaya
Keywords: Collection climate; Cuttings, clonal plant production; Exotic fruit production; Hylocereus undatus Haw; Sustainability